Beta-hydroxybutyrate, an endogenous NLRP3 inflammasome inhibitor, attenuates anxiety-related behavior in a rodent post-traumatic stress disorder model - Takehiko Yamanashi (Nature Portfolio, 2020)
Abstract Accumulating evidence suggests that elevated inflammation contributes to the pathophysiology of post-traumatic stress disorder (PTSD) and that anti-inflammatory drugs might be a new treatment strategy for PTSD. It has been reported that beta-hydroxybutyrate (BHB), one of the main ketone bodies produced, can have an anti-inflammatory and antidepressant effect. Here, we investigated the potential anti-anxiety and anti-inflammatory effects of BHB using a rodent PTSD model, induced by single prolonged stress (SPS). Male, Sprague–Dawley rats were employed in this study. Repeated administration of BHB attenuated SPS-induced anxiety-related behaviors evaluated by the elevated plus maze test. SPS increased the serum levels of TNF-α and IL-1β. In contrast, BHB administration partially attenuated the increase of serum TNF-α. These findings demonstrate that BHB exerts its anxiolytic effects, possibly by inhibiting systemic TNF-α. Hence, BHB may be a novel therapeutic candidate for the treatment of PTSD.